A comprehensive review of heat transfer intensification methods for latent heat storage units. Issue 1 (19th January 2020) - Elarem, Raja; Alqahtani, Talal; Mellouli, Sofiene; Askri, Faouzi; Edacherian, Abhilash; Vineet, Tirth; Badruddin, Irfan Anjum; Abdelmajid, Jemni
Abstract: Latent heat thermal energy storage (LHTES) systems and their applications have been very substantive for the developments in energy science and engineering. The efficiency of LHTES systems largely depends on the thermal conductivity of the phase change materials (PCMs) and the heat transfer mechanisms in them. This review focuses on the methods employed to enhance heat transfer in LHTES systems which accordingly improve their storage performance. This includes the possible geometrical configurations of LHTES systems and the effects of their design parameters. The various methods adopted for enhancing LHTES systems' performance through either applying nanomaterials additives, using cascaded or encapsulated PCMs, or employing extended surfaces, such as fins, are discussed in detail. Additionally, various designs of PCM based heat exchangers with active and passive heat transfer techniques were highlighted. These systems are critically analyzed to help selecting reliable techniques and compatible materials for effective designs in order to achieve more efficient LHTES systems. This review would be helpful for the researchers to further develop heat transfer intensification mechanisms in LHTES systems. Abstract :